Studi Penggunaan Bolus Berbahan Silicone Rubber terhadap Dosis Permukaan pada Radioterapi Berkas Elektron - Gede Wiratma Jaya; Heri Sutanto; Eko Hidayanto; Galih Puspa Saraswati (Progressive Physics Journal, 2020)
Radiotherapy is a method of externally cancer therapy using a Linear Accelerator (LINAC) tool. LINAC can produce photon and electron beam energy which will be used to treat cancer according to the position of the cancer in the patient's body. When using an electron beam to treat cancer on the surface of the skin, it is found that there is a lack of a radiation dose. The use of bolus with Silicone Rubber (SR) material is a solution to provide an increase in radiation doses in the surface area of the skin. In this study SR boluses were made using the sol-gel method with dimensions of 17 cm x 17 cm x 1 cm. The SR Bolus was illuminated with an applicator field area of 10 cm x 10 cm and energy variations of 5 MeV and 7 MeV. The surface dose produced at the moment without using a bolus for 5 MeV and 7 MeV energy is 1.60 Gy and 1.61 Gy. When using bolus, the surface dose of 5 MeV and 7 MeV energy is 2.12 Gy and 2.06 Gy. From the results of this study it can be concluded that the use of SR bolus can increase a higher surface dose without using bolus.